التعليم عن بعد في الجامعة الجزائرية في زمن كورونا بين الواقع والمأمول - رميشي, ربيعة (جامعة الوادي - University of Eloued, 2023)
فرضت الازمة الصحية الاخيرة التي عرفتها البلاد في مارس 2020 على غلق المؤسسات التعليمية منها الجامعة ،قصد تخفيف من حدة انتشار فيروس كورونا كوفيد19 من جهة ومن جهة أخرى على الجامعات ان تنهي الامتحانات المصيرية التي يوجهها الطلاب ،فهذه الظروف دفعت بالجامعات الى اتخاذ اساليب وتدابير علمية تعمل كبديل عن الطريقة التقليدية التي تقوم على الحضور والمقابلة المباشرة بين الاستاذ والطالب في هذه العملية الى استعمال التكنولوجية في استخدام تقنية جديدة كبديل انسب لصمان استمرار العملية التعليمية ودراية احتياجات الطلابية ،الا ان تفعيل هذه التقنية عن طريق الموقع الرسمي الذي استخدمته الجامعات عبر وسائل التكنولوجية من خلال الانترنيت ولّد تحديا واقعيا وذلك لضعف تدفقها بشكل اوسع على مناطق وجود محور العملية التفاعلية التي تربط بين الاستاذ والطالب في هذه العملية التعليمية مع صعوبة استخدام وشائل التكنولوجية اتي تضمن السير الحسن للمنظومة التعليمية الجامعية. abstract: The recent health crisis that our country experienced in March 2020 forced the closure of educational institutions, including universities, in order to mitigate the spread of the Covid 19 virus on the one hand, and on the other hand, universities must finish the fateful exams directed by students, as these circumstances prompted universities to take scientific methods and measures It works as an alternative to the traditional method that is based on attendance and a direct interview between the professor and the student in this process, to the use of technology in the use of new technology as a more appropriate alternative to ensure the continuation of the educational process and the study of student needs , However activating this technology through the official website that the universities used through technological means through the Internet generated a realistic challenge due to the weak flow of more broadly on the areas of the interactive process that connects the professor and the student in this educational process, with the difficulty of facing this circumstance using technological means. In achieving this by the student and the professor together In This study we use the descriptive method and the questionnaire tool
دراسة لعينة من الطلبة بجامعة مولود معمري تيزي وزو
مقال
Keywords: تعليم عن بعد (تعليم الكتروني ) ،جائحة كورونا ،تحصيل جامعي ،تدفق الانترنيت ،صعوبة استخدام التكنولوجية; distance education (e-learning), the corona pandemic, university achievement, Internet flow, difficulty using technology